Pore density of the benthic foraminiferal test responded to the hypoxia off the Changjiang estuary in the East China Sea - Wang, Feifei; Yang, Shixiong; Zhai, Bin; Gong, Shaojun; Wang, Junjie; Fu, Xiaojin; Yi, Jian; Ning, Ze (Frontiers in Marine Science, 2023)
The benthic foraminiferal assemblages are commonly used to indicate different oxygenation conditions. In the last few decades, pore characteristics of the benthic foraminiferal tests from the micro-perspective using high-spatial-resolution analysis have been extensively suggested to indicate redox changes. Based on the whole test of the living shallow-infaunal species Bolivina robusta using a more representative and comprehensive method, we observed a significant negative correlation between the pore density (PD) and bottom dissolved oxygen (DO) concentration, and the average PD was about 36% higher in hypoxic environments (DO<3 mg/l) than in oxic environments (DO>3 mg/l). In terms of reproduction pattern in hypoxic environments, the species seemed to mainly choose the asexual life cycle (74.60%) to get more small generations with larger pore size (PS) (asexual 7 μm vs. sexual 4 μm) and exterior ornamentation (irregular papillae) as their survival strategy. The results provide new insight into the benthic foraminiferal ecology to reconstruct the pale-oceanography and paleo-ecology changes in the East China Sea. Moreover, this study has the potential to be applied in broad regions as an independent proxy by comparison to other widely-distributed benthic foraminiferal species.